Scientific basis of tobacco product regulation report of a WHO study group. (Technical report series (World Health Organization), 2007)
This report presents the conclusions reached and recommendations made by the members of the WHO Study Group on Tobacco Product Regulation at its third meeting, during which it reviewed four background papers specially commissioned for the meeting and which dealt, respectively, with the following four themes. 1) the contents and design features of tobacco products: their relationship to dependence potential and consumer appeal; 2) Candy-flavoured tobacco products: research needs and regulatory recommendations; 3) Biomarkers of tobacco exposure and of tobacco smoke-induced health effects; 4) Setting maximum limits of toxic constituents in cigarette smoke. The Study Group's recommendations in relation to each theme are set out at the end of the section dealing with that theme and overall recommendations are summarized at the end. The report is complemented by 2 Annexes containing reports and other documents arising from meetings of the WHO Scientific Advisory Committee on Tobacco Products Regulation (SACTob) and reports and other documents arising from meetings of the WHO Study Group on Tobacco Products Regulation (TobReg).